α-Synuclein: A Multifunctional Player in Exocytosis, Endocytosis, and Vesicle Recycling - Huang, Mingzhu; Wang, Bianbian; Li, Xiaopeng; Fu, Chongluo; Wang, Changhe; Kang, Xinjiang (Frontiers in Neuroscience, 2019)
α-synuclein (α-Syn) is a presynaptic enriched protein involved in the pathogenesis of Parkinson’s disease. However, the physiological roles of α-Syn remain poorly understood. Recent studies have indicated a critical role of α-Syn in the sensing and generation of membrane curvature during vesicular exocytosis and endocytosis. It has been known to modulate the assembly of SNARE complex during exocytosis including vesicle docking, priming and fusion steps. Growing evidence suggests that α-Syn also plays critical roles in the endocytosis of synaptic vesicles. It also modulates the availability of releasable vesicles by promoting synaptic vesicles clustering. Here, we provide an overview of recent progresses in understanding the function of α-Syn in the regulation of exocytosis, endocytosis, and vesicle recycling under physiological and pathological conditions.